Pemahaman Hadis Yusuf al-Qardhāwy: Telaah atas Kaidah al-Tamyīz Bayna al-Wasīlah al-Mutaghayyirah wa al-Hadhf al-Thābit - Eko Zulfikar (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2019)
Abstract: As the second legacy of Islamic teachings after the al-Qur’an, hadith is a set of teachings that provide various guiding solutions to navigate the dynamics of life. It is very reasonable if comprehending the hadith comprehensively is very necessary to find the meaning of a hadith based on the development and demands of the times. This paper discusses the construction of the understanding hadith offered by Yusuf al-Qardhawy in the book Kayfa Nata’amal ma’a al-Sunnah al-Nabawiyyah. From several methods offered by al-Qardawy in the book, the author specifies on one of his rules, namely al-Tamyiz Bayna al-Wasilah al-Mutaghayyirah wa al-Hadhf al-Thabit. By reading it from the perspective of constructivism, purely library research and analysis of intercontextual data, it is found that understanding in addition to al-Qardhawy in using this rule always relates hadith with something current and always up to date, he also tries to apply it to elastic traditions of regional conditions and open to the times.